Міграційні наміри студентської молоді та їх вплив на мотиваційну складову людського капіталу України - Мельничук, Д.П. (Інститут демографії та соціальних досліджень НАН України, 2009)
В статье проанализировано влияние миграционных намерений студенческой молодёжи на качественные характеристики мотивационной компоненты человеческого капитала Украины. С целью определения содержания миграционных стремлений выпускников ВУЗов и уточнения причин, которые их провоцируют, автором проведено исследование
предпочтений студенческой молодёжи, результаты которого и легли в основу представленной статьи. In the article influence of students’ migratory intentions on qualitative characteristic of motivational component of human capital of Ukraine is analyzed. Initial supposition was an assumption that from one side – stirring up of outside migration including labour migration poses a threat for stable development of the country at the period of postindustrial society; from other side – nowadays migratory level of society is one of the most important indirect criterion of motivational field diagnostic that was formed in any society. With the aim of determination of migratory aspiration of graduates and specification of the reasons that induce them it was carried out exploration by the author. The results of the research are presented in the article below.